A manual of elementary physical education skill theme activities for physical education specialists to use in collaboration with classroom teachers - Mustain, Wendy C. (Virginia Tech, 2014)
Quality daily physical education is a necessary ingredient in the lives of elementary school children. Daily physical education has been supported by Secretary of Education, William T. Bennett, the U.S. Congress, the American Medical Association, successful programs in France, Canada, and Australia, and extensive educational research. Its inclusion in elementary curricula is commonplace. In fact, in the state of California, the teaching of physical education at the elementary level is mandated by law. === Master of Science